Plans and projects for sustainable development: The experience of the Urbanism I A chair (ARQUISUR Revista, 2015)
The Urbanism I A Chair of the Faculty of Architecture, Urbanism and Design of the National University of Córdoba, considers it essential to educate students in the construction of a critical and reflective thought, based on models, theories and methodologies concerned with sustainable development of our cities. This Chair promote the construction of a holistic vision on the city, addressing the issues, methodologies and specific instrumentation —master plans, urban projects— from traditional approaches: physical–functional and morphological–perceptual, which complements a socio–environmental vision of the urban phenomenon. This paper present a synthesis of the academic task we develop.
Keywords: eco–urban project; master plan; sector; sustainability; urban development